IDENTIFIKASI SIFAT KIMIA TANAH YANG DITANAMI TANAMAN KENTANG (SOLANUM TUBEROSUM L.) DI DESA PINASUNGKULAN UTARA KECAMATAN MODOINDING - Michael A.S Roring; Diane D. Pioh; Jemmy Najoan (COCOS, 2020)
ABSTRATC Soil chemical properties are very influential to increase plant growth. Application of fertilizer is one of the important means of production in plant cultivation, so that its availability is absolutely necessary for the sustainability of soil and plant productivity. The function of chemical fertilizers is to provide macro nutrients such as N, P, K, Ca, Mg, and S and micro nutrients such as Zn, Cu, B, Mo, Co, Mn, Fe. This study aims to identify the chemical properties of soil planted with potato (Solanum Tuberosum L.) in Pinasungkulan Utara Village, Modoinding District. The results showed that the soil pH content was in neutral conditions (6.5 - 6.8), Corganic had a low to moderate value (1.32% - 2.78%), Nitrogen had a low to moderate value ( 0.2% - 0.24%), Soil phosphorus has a moderate content value (17.51ppm - 20.65ppm), potassium. Based on the chemical properties of land planted with potato (Solanum Tuberosum L.) in Pinasungkulan Utara Village, Modoinding District, there are no serious problems but attention needs to be given to improving the management of organic matter. Keywords: Identification, Chemical Properties, Potato Plants.